PENGARUH KUALITAS PRODUK, HARGA, KEPERCAYAAN MEREK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN KAMERA DIGITAL CANON DI SEMARANG - Imam Nuryanto; Ichlasul Naufal Hakim (Lembaga Pengembangan Kinerja Dosen, 2021)
Purchasing decision are the decision of consumers to buy a product that previously thought about worthy or not to buy the product by considering the information that is known by the reality of the product after seeing it. There are several factors that affect the purchasing decision, namely the product quality, price, brand trust and brand image. The object of the research is Canon digital cameras which are on Top Brand Index in 2014-2018, where the Canon digital cameras always ranked at the top. But here the Canon digital cameras has proved that when many competitors are surrounded, Canon digital cameras has always ranked first on the TBI and the digital camera Canon's product is superior to other products. The purpose of the research was to analyze the influence of the product quality, price, brand trust and brand image on purchasing decision. The population of the research was that consumers who ever and wear the camera Canon digital, a company based in Semarang and aged over 17 years. The numbers are unknown and sample taken 100 respondents. Sample technique by using purposive sampling. The type of data used is. primary data, method of data collection using the questionnaire and analysis techniques used is multiple linear regression. The results of the analysis showed: product quality has a positive and significant influence on purchasing decision, price proved to have a positive and significant influence on purchasing decision, brand trust significant has a positive and influence on purchasing decision, brand image proved to have a positive and significant influence on purchasing decision.